Assessing aberrant salience in young community help‐seekers with early psychosis: The approved Italian version of the Aberrant Salience Inventory. Issue 3 (7th October 2020) - Pelizza, Lorenzo; Azzali, Silvia; Garlassi, Sara; Scazza, Ilaria; Paterlini, Federica; Chiri, Luigi R.; Poletti, Michele; Pupo, Simona; Cicero, David C.; Preti, Antonio; Raballo, Andrea
Abstract: Objectives: Aberrant salience (AS) has a crucial role in the onset of psychosis. The Aberrant Salience Inventory (ASI) is the only self‐report instrument specifically developed for the assessment of AS. Aim of this study was to examine the reliability and the validity of the approved Italian version of the ASI in a clinical sample of young help‐seekers. Methods: The ASI was completed by 204 individuals, aged 13–35 years. Reliability was assessed examining internal consistency and test‐retest reliability. Concordant validity was established with CAARMS ("Comprehensive Assessment of At‐Risk Mental States"). Results: The ASI showed high test‐retest reliability and excellent internal consistency. The ASI total score had significant positive correlations with CAARMS "Positive Symptoms" subscores. Conclusions: The ASI showed satisfactory psychometric properties and seems to be a suitable instrument for early detection of psychosis in Italian mental health services.